(untitled) (Research, Society and Development, 2019)
To say that the act of reading is fundamental, it is already something of the common sense. However, it is important that we reflect how reading is related to knowledge and how the different conceptions of reading influence in the act of reading. Thus, starting from a philosophical reflection of knowledge, this article proposes to establish a dialogue with the linguistic bias of the text and reading in order to demonstrate how the understanding of reading interferes in the acquisition of knowledge. For this, we carried out a descriptive and qualitative research, based on a literature review, by which we anchor ourselves, mainly in the studies of Coscarelli and Cafieiro (2013); Rojo and Moura (2012) and Soares (2012). Furthermore, in order to demonstrate how the conception of reading interferes with the understanding of the text, we analyze a strip in order to explain this association between the concept of reading and the way in which we assume the textual information. Through this reflection, we perceive that the conception of reading adopted interferes directly with the act of reading. Thus, it is important that reading do not be limited to the decoding of words, but rather it constitutes as a means of interaction and of (re) construction of the individuals.